Nanonets Derived from Turnip Mosaic Virus as Scaffolds for Increased Enzymatic Activity of Immobilized Candida antarctica Lipase B - Cuenca, Sol; Mansilla, Carmen; Aguado, Marta; Yuste-Calvo, Carmen; Sánchez, Flora; Sánchez-Montero, Jose M.; Ponz, Fernando (Frontiers in Plant Science, 2016)
Elongated flexuous plant viral nanoparticles (VNPs) represent an interesting platform for developing different applications in nanobiotechnology. In the case of potyviruses, the virion external surface is made up of helically arrayed domains of the viral structural coat protein (CP), repeated over 2000 times, in which the N- and C-terminal domains of each CP are projected toward the exterior of the external virion surface. These characteristics provide a chemical environment rich in functional groups susceptible to chemical conjugations. We have conjugated Candida antarctica lipase B (CALB) onto amino groups of the external surface of the potyvirus turnip mosaic virus (TuMV) using glutaraldehyde as a conjugating agent. Using this approach, TuMV virions were transformed into scaffolds for CALB nanoimmobilization. Analysis of the resulting structures revealed the formation of TuMV nanonets onto which large CALB aggregates were deposited. The functional enzymatic characterization of the CALB-bearing TuMV nanonets showed that CALB continued to be active in the nanoimmobilized form, even gaining an increased relative specific activity, as compared to the non-immobilized form. These novel virus-based nanostructures may provide a useful new approach to enzyme nanoimmobilization susceptible to be industrially exploited.